Ultrastructural features of Catharanthus roseus leaves infected with cucumber mosaic virus - Mamat, Mazidah; Lau, Wei Hong; Yusoff, Khatijah; Hashim, Habibuddin; Tan, Yee How (Universiti Putra Malaysia Press, 2012)
Catharanthus roseus var. rosea, infected with Malaysian isolate of cucumber mosaic virus (CMV-MP), exhibited leaf mosaic, leaf deformation and malformed flowers. Electron microscopic examination of the infected leaf cells revealed significant alteration of the chloroplasts in the mesophyll cells. Large starch grains in necrotic zones and disorganized thylakoid system were the most prominent modifications observed within the chloroplasts of the infected tissues. Meanwhile, membrane-bound vesicles were detected in the vacuoles of the CMV-MP-infected leaf cells. A crystalline array of phytoferritin macromolecules was detected in the chloroplast at 40 days post-inoculation. However, neither single nor aggregate of CMV-MP particles was detected in the cytoplasm due to difficulties in differentiating them from the ribosomes. Nonetheless, structure resembling the inclusion bodies, commonly produced after virus infection, could not be found in the infected leaf cells. Similarly, structure abnormality in the nucleus or mitochondria was also not observed.